(3eQGM GdCQhGMs - (3UGMH GdeQGM , CMeO Hf Ydj Hf eSYhO, MSGe GdOjf CHh GdaVGFd,J (B700 (3g` s ((3bQjI TbQI s)
(3ChdgG (B:s
(3bGd GdeaJbQ Edi Gddg GdhOhO CMeO Hf Ydi Hf eSYhO EYde Cf GdUQa Ce GdYdhe hGdfMh CHhgG hjbhi ai GdOQGjGJ OGQhgG s
(3BNQgG (B:s
(3aMQcg GdKGfjI aUGQJ geRI hjLF ai GdHYV HGdMPa hfMh gGY hdGY GdCUd gGFY hdGFY hefg bhdg JYGdi (B" (3hcfJe Ydi TaGLQa YGQGi gGFQ hjLF HGdbdH fMh TGc CUdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B175s
Keywords: (3GdeLGejYs